Alkaline phosphatase activity in an equatorial coral reef ecosystem unrelated to seasonal nutrient dynamics - Nichols, Robert S. (2023)
Coral reef productivity depends on nutrient supply, mediated partly by enzymatic breakdown of organic matter. Alkaline phosphatases hydrolyse phosphomonoesters and are one of the key enzymes involved in marine phosphorus cycling. They are expressed by many marine organisms including planktonic microbes and metazoans such as corals, often in response to phosphate limitation, and are potentially important for coral P nutrition and reef biogeochemical cycling. However, most alkaline phosphatase activity (APA) data are from open-ocean environments, and the rates and drivers of APA in coastal waters are not well understood. Here, we measured both bulk seawater APA and the extracellular APA of three coral species at reefs in Singapore, where the monsoonal ocean current reversal creates strong seasonal changes in dissolved nutrient availability. Seawater APA was always measurable, averaging 9 ± 10 nmol l−1 h−1, but was not correlated with dissolved phosphate or other biogeochemical parameters. Experimental phosphate addition did not reduce seawater APA but addition of labile organic carbon increased seawater APA, indicating that seawater APA was driven by heterotrophic activity rather than phosphate stress. Coral APA ranged from 12 to 163 µmol m−2 h−1 depending on species, which was equivalent to the seawater APA in several metres of the overlying water column. While most coral APA was associated with the coral holobiont rather than the coral mucus, the mucus release added 13–56 µmol m−2 h−1 of APA into the water column, suggesting that corals can potentially contribute significantly to seawater APA.